Stablecoins as the Foundation of DeFi - Nguyen, Jan (2025)
The aim of this thesis is to analyze the rapidly evolving stablecoin industry and to assess whether stablecoins can maintain their peg and function not only as the backbone of the DeFi ecosystem but also as a bridge to traditional finance. The thesis introduces the basic concepts of DeFi, explores the historical evolution, mechanisms, and regulatory frameworks of stablecoins, and examines their use cases both within DeFi and in real-world applications. The practical part provides a comparative analysis of the four largest stablecoins by market capitalization, evaluating their design, collateral models, and risks to better understand their position in the ecosystem.